BALLAST WATER AND BIOINVASION: BRAZILIAN LEGISLATION AND THE PROTECTION OF MARINE ENVIRONMENTAL RISKS - Costa, Beatriz Souza (2016)
This article analyzes the use of water as ballast to balance the vessels, as well as the existing legislation in the country that protects, monitors and punishes those who are responsible for illegal shedding in national jurisdiction waters. That is important, considering ballast water has become a national and international risk with serious consequences such as bioinvasion. It was discovered that ballast water has become one of the fastest forms of marine pollution because it acts quietly. In an attempt to avoid environmental and economic losses, several conventions and international treaties were agreed between countries such as the United Nations Convention on the Law of the Sea, 1982, adopted in Montego Bay. At the national level, Brazil has important institutions for marine environmental protection such as ANVISA, the National Health Surveillance Agency; ANTAQ, National Agency of Waterborne Transport and broad legislation such as Law (6938/81), the National Environmental Policy; the Criminal Environmental Law (9.605/98) and, specifically, NORMAM 20, issued by the Brazilian Navy™s Directorate of Ports and Coasts, which states that every ship to moor at national ports must prove the exchange of ballast water at sea. The research used the legal and theoretical methodology, deductive reasoning and literature from technical and government sites. The results show that Brazil has a concern over the issue and the national legislation proves the effort to prevent marine pollution. However, research in the field is necessary so that invading organisms are discovered prior to the pollution. In addition to that, legislation and supervision must be improved.